2021
DOI: 10.1177/11206721211005703
|View full text |Cite
|
Sign up to set email alerts
|

Aflibercept in real-life for the treatment of age-related macular degeneration using a treat and extend protocol: The Armada study

Abstract: Purpose: To report the visual and anatomic outcomes in treatment-naïve neovascular age-related macular degeneration (nAMD) patients treated with aflibercept under a standardized Treat and Extend (T&E) protocol for up to 3 years of follow-up in “real-life” practice. Methods: This retrospective, observational, multicenter study included patients with treatment-naïve nAMD and at least 12 months of follow-up. T&E regimen adjustment was initiated after loading phase. At each visit best-corrected visual acui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 38 publications
4
4
0
Order By: Relevance
“…Other studies have shown different distributions of the CNV subtypes, with subtype 1 found in 34-61% of eyes and subtype 3 in 2-40% of eyes [22,[25][26][27]. The predominance of type 1 CNV in our study is in accordance with the recent publications by Mathis et al [28,29].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Other studies have shown different distributions of the CNV subtypes, with subtype 1 found in 34-61% of eyes and subtype 3 in 2-40% of eyes [22,[25][26][27]. The predominance of type 1 CNV in our study is in accordance with the recent publications by Mathis et al [28,29].…”
Section: Discussionsupporting
confidence: 92%
“…Many pivotal prospective studies have reported higher rates of eyes treated Q12W from 42 to 60% in the ARIES ALTAIR and VIEW studies [4, 20, 21]. Our results are closer to the rates of 32–37% reported in the recent real-life studies with a shorter follow-up [2224]. However, our study being cross-sectional, our cohort included all eyes injected during a fixed period regardless of the protocol initially used (directly and lately treated with the TE regimen).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations